Training Sequence-Based Chromatic Dispersion Estimation With Ultra-Low Sampling Rate for Optical Fiber Communication Systems - Yiwen Ma; Peng Guo; Aiying Yang; Lingwei Zhuang; Shaojian Guo; Yueming Lu; Yaojun Qiao (IEEE Photonics Journal)
We present a novel method to estimate chromatic dispersion with ultra-low sampling rate based on training sequence. The under-sampling can be equivalent to over-sampling by splicing points with periodic sequence. The functional relationship between equivalent over-sampling rate and symbol rate, actual sampling rate and sequence period is deduced. To demonstrate the feasibility of the method, the simulation of a 28 GBaud QPSK optical fiber communication system is carried, in which 76 MSa/s sampling rate is equivalent to 66.5 GSa/s sampling rate. The results show that maximum estimation error is less than 160 ps/nm after 100 km to 2300 km SSMF transmission. We also demonstrate the robustness of the proposed method to amplified spontaneous emission and nonlinear noise in a three-channel optical fiber communication system. Moreover, the proposed method has been experimentally verified with a 20.5 GBaud QPSK system, 1.25 GSa/s sampling rate is equivalent to 51.25 GSa/s sampling rate, and estimation error is less than 100 ps/nm and 150 ps/nm after 100 km and 200 km SSMF transmission, respectively. The proposed method eliminates the requirement of high speed ADC and is cost effective, which can be used for optical performance monitoring.